2020
DOI: 10.21829/abm127.2020.1717
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive method for estimating leaf area of Erythroxylum pauferrense (Erythroxylaceae) from linear dimensions of leaf blades

Abstract: Background and Aims: Determining the leaf area is essential for studies on growth, propagation, and ecophysiology of forest species. Developing quick, practical, and accurate methods is needed to estimate leaf area without destroying leaves. Therefore, this research aimed to obtain an equation from regression models that meaningfully estimate the leaf area of Erythroxylum pauferrense using linear dimensions of its leaf blades.Methods: For this purpose, 1200 leaves were randomly collected from different plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(46 reference statements)
5
5
0
Order By: Relevance
“…Therefore, the number of leaves ( 200) evaluated in the present study was meaningful for estimating the leaf area of P. colorata using dimensions of its leaf blades. Moreover, high variation in product of length by width and real leaf area was also observed in previous studies (Leite et al 2017;Ribeiro et al 2018a;Ribeiro et al 2020a).…”
Section: Resultssupporting
confidence: 79%
“…Therefore, the number of leaves ( 200) evaluated in the present study was meaningful for estimating the leaf area of P. colorata using dimensions of its leaf blades. Moreover, high variation in product of length by width and real leaf area was also observed in previous studies (Leite et al 2017;Ribeiro et al 2018a;Ribeiro et al 2020a).…”
Section: Resultssupporting
confidence: 79%
“…The present study showed that the best equations to estimate the LA of peanut cultivars were those that used LW, compared to equations that used only one leaflet dimension (L or W), with the best criteria and adjustments of the models used (Guimarães et al 2019, Macário et al 2020, Goergen et al 2021, except for the exponential model, in which the best equations were those that used L of the leaflets (Ribeiro et al 2020).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the number of leaves (200 leaves) used in this study was adequate to estimate the leaf area of E. velutina through linear dimensions of the central leaflet. Other studies also reported high variation in product of length by width, product of length by length, product of width by width, and real leaf area (RIBEIRO et al, 2020b).…”
Section: Discussionmentioning
confidence: 86%
“…As compared to the equations fitted using length or width, those equations adjusted using the product of length by width (LW) showed the best assumptions for estimating leaf area, thus best fitting the regression models (RIBEIRO et al, 2019b). Except for the equation adjusted using the exponential model, which showed the best indexes when using leaflet width (W) (RIBEIRO et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%